2015
DOI: 10.1387/ijdb.150172mz
|View full text |Cite
|
Sign up to set email alerts
|

3D culture of ovarian follicles: a system towards their engineering?

Abstract: Infertility in women is a health priority. Designing a robust culture protocol capable of attaining complete follicle growth is an exciting challenge, for its potential clinical applications, but also as a model to observe and closely study the sequence of molecular events that lie behind the intricate relationship existing between the oocyte and surrounding follicle cells. Here, we describe the procedures used to maintain the ovarian follicle 3D architecture employing a variety of in vitro systems and several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…In vitro maturation (IVM) of follicles and oocytes is a suitable strategy for fertility preservation of infertile patients . Several culture systems have been developed for the IVM of follicles, similar to the ovarian microenvironment, which yield different results . IVM could be a method for monitoring the effect of the vitrification procedure on follicular development and oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro maturation (IVM) of follicles and oocytes is a suitable strategy for fertility preservation of infertile patients . Several culture systems have been developed for the IVM of follicles, similar to the ovarian microenvironment, which yield different results . IVM could be a method for monitoring the effect of the vitrification procedure on follicular development and oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…To create scaffolds for oocyte in vitro culture, various natural biomaterials such as the physiological components of extra‐cellular matrix (ECM; collagen and hyaluronic acid) or inert polymers (alginate), have been used. Promising results in terms of oocyte meiosis resumption and achievement of full competence have been obtained in various species (Dorati et al., ; Morselli, Canziani, Vigo, & Luvoni, ; Morselli, Vigo, & Luvoni, ; Pangas, Saudye, Shea, & Woodruff, ; Songsasen, Comizzoli, Nagashima, Fujihara, & Wildt, ; Zuccotti et al., ). The preliminary application of coculture systems in a 3D alginate microenvironment resulted in the resumption of meiosis in domestic cat oocytes, but the in vitro embryo development was not investigated (Morselli et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…This review focuses on follicular interactions in the ovary. Studying individual follicles is important in investigating follicular development and many researchers have cultured isolated follicles to elucidate the regulatory mechanism of follicular development . These studies revealed interactions among oocytes, granulosa cells, and theca cells and the factors that are produced by these cells .…”
Section: Methods Of Observing Thedynamics and Regulatory Mechanisms Omentioning
confidence: 99%
“…Studying individual follicles is important in investigating follicular development and many researchers have cultured isolated follicles to elucidate the regulatory mechanism of follicular development. [69][70][71][72][73][74][75][76] These studies revealed interactions among oocytes, granulosa cells, and theca cells and the factors that are produced by these cells. 61,65,66 These results described the regulatory mechanisms of follicular development within a follicle, but were not able to determine the mechanism in the ovary.…”
Section: Interaction Of Follicles In the Ovary To Coordinate Follicmentioning
confidence: 99%